2019
DOI: 10.18297/jri/vol3/iss1/3
|View full text |Cite
|
Sign up to set email alerts
|

Severity of disease and mortality for hospitalized patients with community-acquired viral pneumonia compared to patients with community-acquired bacterial pneumonia

Abstract: Background: There exists a large body of literature to help identify, diagnose, treat, and manage community-acquired pneumonia (CAP). Despite this, there is little data that directly compares the clinical syndromes and complications of pure bacterial pneumonia to pure viral pneumonia. Our study compares the clinical presentation, morbidity and mortality of viral vs. bacterial etiologies of CAP. Methods: This was a secondary data analysis of the Community-Acquired Pneumonia Organization (CAPO) international stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Regarding the PSI, our results do not confirm the data from Kim et al, 15 who observed no differences in this score, between viral and bacterial CAP, nor in mortality between these two groups (15% and 16%, respectively). However, our results agree with those from other authors who evaluated disease severity in the setting of viral versus bacterial CAP 35 . Their results showed that bacterial CAP more frequently had PSI ≥ class IV, despite the fact that viral CAP significantly showed higher frequencies of ICU admission, intubation, and in hospital mortality, concluding that PSI scores cannot be used to accurately predict the outcome in viral CAP 35 …”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Regarding the PSI, our results do not confirm the data from Kim et al, 15 who observed no differences in this score, between viral and bacterial CAP, nor in mortality between these two groups (15% and 16%, respectively). However, our results agree with those from other authors who evaluated disease severity in the setting of viral versus bacterial CAP 35 . Their results showed that bacterial CAP more frequently had PSI ≥ class IV, despite the fact that viral CAP significantly showed higher frequencies of ICU admission, intubation, and in hospital mortality, concluding that PSI scores cannot be used to accurately predict the outcome in viral CAP 35 …”
Section: Discussionsupporting
confidence: 86%
“…However, our results agree with those from other authors who evaluated disease severity in the setting of viral versus bacterial CAP. 35 Their results showed that bacterial CAP more frequently had PSI ≥ class IV, despite the fact that viral CAP significantly showed higher frequencies of ICU admission, intubation, and in hospital mortality, concluding that PSI scores cannot be used to accurately predict the outcome in viral CAP. 35 The low number of deaths and patients per PSI and CURB-65 scores risk classes, especially in the viral CAP group, are limitations of this study to confirm our findings regarding the usefulness of the severity scores, especially in the viral etiology.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations